The relationship between creative thinking skills, opportunity identification skills, and problem-solving abilities among biology education students - Ika Wardani; M. Arsyad (Practice of The Science of Teaching Journal: Jurnal Praktisi Pendidikan, 2026)
Understanding of the relationship among creative thinking, opportunity identification, and problem-solving skills among biology education students remains limited. These competencies are essential for fostering innovative, contextual, and SDG-oriented biology learning. This study aims to analyze the relationship between creative thinking skills, opportunity identification skills, and problem-solving abilities among biology education students.The study was motivated by the limited number of studies that simultaneously integrate these three skills within the context of biology education. The research employed a quantitative approach with a correlational design. The research sample consisted of 405 biology education students from several universities in East Java, selected using simple random sampling. The research instruments comprised tests and questionnaires that had been validated for validity and reliability. Data analysis utilized prerequisite tests (normality, linearity, and multicollinearity), Pearson’s correlation test and multiple linear regression. The results indicated that creative thinking skills (r = 0.175; p < 0.05) and opportunity identification skills (r = 0.228; p < 0.05) had a positive and significant relationship with problem-solving abilities. Simultaneously, both variables had a significant effect (F = 15.824; p < 0.05) with a contribution of 7.3% (R² = 0.073), whereby the ability to identify opportunities had a more dominant influence. These findings highlight the importance of developing these skills in an integrated manner within biology education to support the Sustainable Development Goals (SDGS). Abstrak. Pemahaman mengenai hubungan antara keterampilan berpikir kreatif, identifikasi peluang, dan pemecahan masalah pada mahasiswa pendidikan biologi masih terbatas. Padahal, ketiga keterampilan tersebut merupakan kompetensi penting untuk mendukung pembelajaran biologi yang inovatif, kontekstual, dan berorientasi pada pencapaian SDGs. Penelitian ini bertujuan untuk menganalisis hubungan antara keterampilan berpikir kreatif, keterampilan mengidentifikasi peluang, dan keterampilan pemecahan masalah pada mahasiswa pendidikan biologi. Penelitian ini dilatarbelakangi oleh masih terbatasnya kajian yang mengintegrasikan ketiga keterampilan tersebut secara simultan dalam konteks pendidikan biologi. Penelitian menggunakan pendekatan kuantitatif dengan desain korelasional. Sampel penelitian berjumlah 405 mahasiswa pendidikan biologi dari beberapa perguruan tinggi di Jawa Timur yang dipilih menggunakan teknik simple random sampling. Instrumen penelitian berupa tes dan angket yang telah diuji validitas dan reliabilitasnya. Analisis data menggunakan uji prasyarat (normalitas, linearitas, dan multilkolinearitas), uji korelasi Pearson dan regresi linear berganda. Hasil penelitian menunjukkan bahwa keterampilan berpikir kreatif (r = 0,175; p < 0,05) dan keterampilan mengidentifikasi peluang (r = 0,228; p < 0,05) memiliki hubungan positif dan signifikan dengan keterampilan pemecahan masalah. Secara simultan, kedua variabel berpengaruh signifikan (F = 15,824; p < 0,05) dengan kontribusi sebesar 7,3% (R² = 0,073), di mana keterampilan mengidentifikasi peluang memiliki pengaruh yang lebih dominan. Temuan ini menunjukkan pentingnya pengembangan keterampilan tersebut secara terintegrasi dalam pembelajaran biologi untuk mendukung tujuan Pembangunan Berkelanjutan (SDGs).